2019
DOI: 10.17159/2221-4070/2018/v8i1a4
|View full text |Cite
|
Sign up to set email alerts
|

Inside a Box: Using Objects To Collaboratively Narrate Educator Experiences of Transformation in Higher Education

Abstract: This article is a reflection on the use of object memory in creating a collaborative artsbased narrative that explores educator experiences with transformation in higher education. The collaborative arts-based narrative that I present here emerged from my doctoral thesis in which I collaborated with participants to explore how our memories and experiences could help us understand and approach issues of social justice in education. In this article, I reflect on the way in which memory objects guided the creatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This was combined with Kara's (2015) creative research methods approach which makes use of artefacts such as photographs, articles and drawings that hold specific memories or relevance for the participant. The artefacts acted as a 'springboard' for discussing important events and the research participants found the process of choosing and sharing the items made material (Müller, 2019) some of the more abstract aspects that had influenced their decisions.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…This was combined with Kara's (2015) creative research methods approach which makes use of artefacts such as photographs, articles and drawings that hold specific memories or relevance for the participant. The artefacts acted as a 'springboard' for discussing important events and the research participants found the process of choosing and sharing the items made material (Müller, 2019) some of the more abstract aspects that had influenced their decisions.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…In response, they offered a methodological strategy that explores externalised examples of imagination such as writings, self-reports or other artifacts, and multimodal texts. An externalised imagination could take the form of narrative and storytelling, both of which have already been considered as strategies toward achieving transformation and social change (Müller, 2019;Razack, 2006). Graef et al (2020) considered storytelling's "co-constructed and dynamic nature" to be the driver of "social and political change" (p. 433).…”
Section: Imagination and Storying: A Framework For Studying Social Changementioning
confidence: 99%